1999
DOI: 10.1359/jbmr.1999.14.6.856
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Importance of the 1,25(OH)2D3 Membrane Receptor and Evidence for a Membrane Receptor Specific for 24,25(OH)2D3

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 44 publications
3
58
2
1
Order By: Relevance
“…It is also possible that some of the effects were due to traditional steroid hormone receptor mechanisms, although controversy exists as to whether chondrocytes have nuclear receptors for 24R,25-(OH) 2 D 3 (Garabedian et al, 1978;Kato et al, 1998;St.-Arnaud and Glorieux, 1998). Despite these caveats, the results reported here support the hypothesis that proliferation, differentiation, and matrix production are regulated in part via PKC, and this is regulated through both genomic and nongenomic pathways via the 24R,25-(OH) 2 D 3 membrane receptor (Kato et al, 1998;Pedrozo et al, 1999b).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is also possible that some of the effects were due to traditional steroid hormone receptor mechanisms, although controversy exists as to whether chondrocytes have nuclear receptors for 24R,25-(OH) 2 D 3 (Garabedian et al, 1978;Kato et al, 1998;St.-Arnaud and Glorieux, 1998). Despite these caveats, the results reported here support the hypothesis that proliferation, differentiation, and matrix production are regulated in part via PKC, and this is regulated through both genomic and nongenomic pathways via the 24R,25-(OH) 2 D 3 membrane receptor (Kato et al, 1998;Pedrozo et al, 1999b).…”
Section: Discussionsupporting
confidence: 52%
“…182:390 -401, 2000. © 2000 Recent evidence has shown that 24R,25-(OH) 2 D 3 exerts effects on chondrocytes in the rat growth plate (Pedrozo et al, 1999b) and chick fracture callus (Kato et al, 1998) through specific 24R,25-(OH) 2 D 3 -activated membrane receptors. The signaling mechanisms involved in the membrane-mediated response include rapid changes in membrane fluidity (Swain et al, 1993) and Ca 2ϩ ion flux (Langston et al, 1990).…”
mentioning
confidence: 99%
“…1␣,25(OH) 2 D 3 has been shown to mediate its effects on enterocytes (49) and osteoblasts (50) via MAP kinase signaling pathways, and the rapid increase in cellular PKC in response to 1␣,25(OH) 2 D 3 can result in increased MAP kinase activity (51). Although 1␣,25(OH) 2 D 3 mediates many of its physiological effects on growth zone chondrocytes through mechanisms that include the 1,25-mVDR-dependent signaling pathways (17), it is important to note that traditional 1,25-nVDR mechanisms are also likely to be involved in the packaging of matrix vesicle PKC in the present study. 1,25-nVDRs are present in the cells, as demonstrated by the presence of immunoreactive receptors in …”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, 24R, 25(OH) 2 D 3 antagonizes an increased opening of L-type Ca 2+ channels evoked by 1,25(OH) 2 D 3 and testosterone (Takeuchi & Guggino 1996). In UMR 106 cells, Li et al (1997) (Nemere et al 1994, Larsson 1999, chick tibial fracture-healing callus (Seo et al 1996, Kato et al 1998) and chondrocytes (Pedrozo et al 1999), suggesting that the rapid actions of 24R,25(OH) 2 D 3 are mediated through a membrane-associated receptor. In mouse osteoblasts and UMR 106 cells, treatment with 24R,25(OH) 2 D 3 results in a release of Ca 2+ from the endoplasmic reticulum and mitochondria (Lieberherr 1987), activation of phospholipase C leading to the formation of inositol 1,4,5-triphosphate (IP 3 ) and diacylglycerol (DAG) (Grosse et al 1993), and activation of protein kinase A and protein kinase C (Li et al 1996).…”
Section: Effects Of 24r25(oh) 2 D 3 and 25(oh)d 3 On Enterocyte Ca 2mentioning
confidence: 99%